Employers' perception towards hiring persons with disabilities - Nor Syazwani, Mohamed Kamil (2018)
Employers’ negative attitudes have long been regarded as a main barrier for employment for persons with disabilities. This is because employer attitudes is presumed to relate with the hiring behavior. Thus, this qualitative study was conducted with the intention to explore employers’ perception towards hiring persons with disabilities. The study involved semi-structure interview with 10 employers from Klang Valley area who haven’t had experience in hiring persons with disabilities. Responses from the respondents indicated that employer are still having negative perception towards person with disabilities. Persons with disabilities are still seen to be helpless who need assistance in doing work, and have limitation in terms of movement, hearing and eyesight. The findings also found that having a policy in hiring persons with disabilities in the workplace does not guarantee that disabled people will be hired. Even if the employers are interested in hiring persons with disabilities, they prefer those who are highly productive; highly independent and possess related qualifications, skills and abilities to perform the given task. Majority of the respondents interviewed also shared that they did not have any experience attending the job coach or return to work program. When asked about the government incentives for those who hired persons with disabilities, majority of them were aware of the incentive and suggested it to be revised and improved. Based on the responses gathered from the interview, several suggestions have been put forward to increase the participation of persons with disabilities in the employment. These include revising the current rewards and incentives given to employers who have hired persons with disabilities; promoting awareness among the employers on the positive side of persons with disabilities and giving equal access to persons with disabilities on education and training so that they have the relevant set of skills that are needed by the industries.